2018
DOI: 10.1055/a-0659-2478
|View full text |Cite
|
Sign up to set email alerts
|

Acute Boldine Treatment Induces Anti-convulsant Effects in Mice through its Antioxidant Activity

Abstract: Boldine is a natural antioxidant that exhibits some important pharmacological properties, which is due to its free radical scavenging effects. And at the same time, reactive oxygen species (ROS) has an important role in pathogenesis of seizure; hence, reducing it via antioxidants like boldine seems to be effective in treating seizure. This study was designed to investigate whether acute treatment with boldine could alter seizures induced by pentylenetetrazole or electroshock in mice. We also evaluated to see i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Boldine, an alkaloid obtained from boldo leaves (Peumus boldus Mol) was reported to have a variety of health benefits including glutathione replenishment, free radical scavenging, anti-inflammatory, antidiabetic, and anticancer effects by virtue of its antioxidant properties. [19][20][21][22][23] In the liver context, the hepatoprotective effect of boldine has been studied against bile-duct ligation induced hepatic fibrosis and cirrhosis in rats. [24] In a study, boldine treatments prevented hepatotoxicity induced by carbon tetrachloride in rats.…”
mentioning
confidence: 99%
“…Boldine, an alkaloid obtained from boldo leaves (Peumus boldus Mol) was reported to have a variety of health benefits including glutathione replenishment, free radical scavenging, anti-inflammatory, antidiabetic, and anticancer effects by virtue of its antioxidant properties. [19][20][21][22][23] In the liver context, the hepatoprotective effect of boldine has been studied against bile-duct ligation induced hepatic fibrosis and cirrhosis in rats. [24] In a study, boldine treatments prevented hepatotoxicity induced by carbon tetrachloride in rats.…”
mentioning
confidence: 99%
“…The findings suggested that different components of MMS-4D showed curative effects against insomnia by regulating different targets and pathways. Among these ingredients, tetrahydroberberine 17 and boldine 18 could be used to treat insomnia, thereby confirming the therapeutic value of MMS-4D for this disease.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, boldine's long-term administration has been associated with augmented levels of glutathione and superoxide dismutase, reflecting its intrinsic antioxidant capabilities (Akotkar et al, 2023). Experimental data prove, Acute administration of noneffective dose of boldine (10 mg/kg) and vitamin C (50 mg/kg) induced anti-convulsing effects of boldine on seizure threshold (Moezi et al, 2019). Its free radical neutralizing activity, especially against hydroxyl radicals, positions boldine as a candidate of considerable interest for epilepsy treatment strategies.…”
Section: Antiseizure Effects Of Pyridine Alkaloids: Gaba Receptor Tar...mentioning
confidence: 96%
“…Its free radical neutralizing activity, especially against hydroxyl radicals, positions boldine as a candidate of considerable interest for epilepsy treatment strategies. These viewpoints collectively expand the treatment landscape for alkaloids in epilepsy management (Moezi et al, 2019). Pyridine alkaloids can also exert their effects by inhibiting synaptic transmission, and tetramethylpyrazine, a pyridine alkaloid derived from Conioselinum anthriscoides (H. Boissieu) Pimenov, is one such compound recognized for its antiseizure properties in clinical settings (Lin J. et al, 2022).…”
Section: Antiseizure Effects Of Pyridine Alkaloids: Gaba Receptor Tar...mentioning
confidence: 99%